2001
DOI: 10.1002/pri.215
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of reproducing hand position when using active compared with passive movement

Abstract: The ability to reproduce hand position accurately is enhanced when position is encoded by active upper extremity movement compared with passive movement. The results have implications for the design of strategies for evaluating as well as treating patients with impaired proprioception and limited movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 23 publications
4
50
0
Order By: Relevance
“…Kalaska 31 suggested that the proprioceptive system may be better tuned to active muscular movements than to movements imposed passively by external forces. This finding is also consistent with the results of Laufer et al, 32 who found that decreased accuracy and greater directional biases when encoding the target location were achieved by passive rather than active movements. Moreover, whereas both active and passive values were affected by military exercise, the increase in JPS errors postexercise was higher for active than for passive values.…”
Section: Discussionsupporting
confidence: 92%
“…Kalaska 31 suggested that the proprioceptive system may be better tuned to active muscular movements than to movements imposed passively by external forces. This finding is also consistent with the results of Laufer et al, 32 who found that decreased accuracy and greater directional biases when encoding the target location were achieved by passive rather than active movements. Moreover, whereas both active and passive values were affected by military exercise, the increase in JPS errors postexercise was higher for active than for passive values.…”
Section: Discussionsupporting
confidence: 92%
“…Given previous research that suggests people are better at localizing their limb after it has been actively moved than when it has been passively positioned (Coslett et al 2008;Laufer et al 2001;Paillard and Brouchon 1968), we thought that the sense of hand position would be less susceptible to proprioceptive recalibration in the active hand placement experiments. The improved ability to localize a limb after an active movement has been attributed to changes in the firing of sensory receptors (Al-Falahe et al 1990;Burke et al 1978a,b;Gandevia et al 1992;Hullinger and Vallbo 1979;Rymar and D'Almedia 1980) and central representations (Prud'homme and Kalaska 1994), including centrally generated neuronal events (i.e., an efference; Gandevia 1987; McCloskey 1980).…”
Section: Influence Of Visuomotor Distortion and Hand Placement On Promentioning
confidence: 94%
“…15 Manual dexterity is also related to the central nervous system, since the cortex receives information from several proprioceptors 8,16 to modulate manual motor tasks increasing movement efficiency. 14,[17][18][19] Hence, if muscle stretching does interfere with these factors it could alter the ability to manipulate objects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Manual dexterity is also related to the central nervous system, since the cortex receives information from several proprioceptors 8,16 to modulate manual motor tasks increasing movement efficiency.…”
mentioning
confidence: 99%